Interventions and Management of Postpartum Hemorrhage: A Literature Review - Dida Rosida; Yanti Hermayanti; Sukmawati S (Universitas Padjadjaran, 2019)
Bleeding is the main cause of maternal mortality in the world, the mortality rate due to bleeding about 30.3% in Indonesia in 2013. Dealing bleeding during and after labor is very important for health professionals including nurses. Research on the management of postpartum hemorrhage is still limited. The purpose of this literature review was to determine the management of postpartum hemorrhage from various countries. The method, this literature review involved articles that published in 2008-2018. The articles searched from several databases, including ProQuest, 32 articles, PubMed 22 articles, and Google 21 scholar articles. Keywords for article search included postpartum hemorrhage, nurse, prevention, treatment, management, and intervention. 75 articles were assessed for the quality using the JBI instrument (Joanna Briggs Institute), and finally, 10 articles were found and met the inclusion criteria. The results show that there are two types of actions to deal with postpartum hemorrhage including direct treatment and indirect treatment. The direct treatment includes bimanual compression, maneuvering techniques, balloon tampons, and tools resembling a butterfly shape for bimanual compression. Indirect actions include training of health workers, initiation of early breastfeeding and ice packs. Conclusion, effective management both directly and indirectly is able to overcome postpartum hemorrhage. Health workers are expected to master effective ways to deal with postpartum hemorrhage.